Association between operative approach and complications in patients undergoing Hartmann's reversal. Issue 8 (21st May 2013) - Cellini, C.; Deeb, A.‐P.; Sharma, A.; Monson, J. R. T.; Fleming, F. J.
<x xml:space="preserve">Abstract</x> Background Complications following reversal of Hartmann's procedure are common, with morbidity rates of up to 50 per cent, and a mortality rate as high as 10 per cent. This is based on case series with heterogeneous data collection and analysis. This study determined risk factors for complications following Hartmann's reversal. Methods Patients who underwent elective open and laparoscopic Hartmann's reversal were identified from the American College of Surgeons National Surgical Quality Improvement Program database (2005–2010). The programme collects patient demographics, preoperative medical history, clinical findings and laboratory investigations. Postdischarge data were obtained by a certified reviewer. Complications were categorized as major, septic or incisional. Risk‐adjusted 30‐day outcomes were assessed by univariable and multivariable analyses, adjusting for patient characteristics, co‐morbidity and operative approach. Results During the study period 7996 patients had a Hartmann's procedure and 2567 cases of Hartmann's reversal were identified, including 336 laparoscopic procedures (13·1 per cent). Major, septic and incisional complication rates were 13·3, 8·5 and 15·7 per cent respectively, with a mortality rate of 0·5 per cent. A laparoscopic approach was found to be independently associated with fewer major (odds ratio (OR) 0·53, 95 per cent confidence interval 0·34 to 0·81), septic (OR 0·48, 0·27 to 0·83) and incisional (OR 0·54, 0·37 to 0·80) complications. A history of chronic obstructive pulmonary disease (OR 1·78–2·00), steroid use (OR 1·75), body mass index at least 30 kg/m2 (OR 1·48), diabetes (OR 1·40), smoking (OR 1·33–1·40), American Society of Anesthesiologists fitness grade III and IV (OR 1·46–1·48) and prolonged operating time (OR 1·02) were other factors associated with complications. Conclusion A laparoscopic approach to Hartmann's reversal was associated with fewer complications than open surgery in this highly selected group of patients.